Eosinophilic Angiocentric Fibrosis as a Stenosing Lesion in the Subglottis. (30th January 2017) - Keogh, Ivan; O'Connell, Rohana; Hynes, Sean; Lang, John
Abstract : Subglottic Eosinophilic Angiocentric Fibrosis (EAF) is an extremely rare disease of an elusive aetiology. It is chronically progressive benign condition that causes narrowing of the subglottic region leading to dysphonia and airway compromise. The diagnosis is historical and imaging is nonspecific. We report a case xc of 56-year-old lady referred to our institution with globus sensation, hoarseness, and mild stridor. Incidental subglottic mass was found at time of diagnostic microlaryngoscopy and biopsy confirmed subglottic EAF. All laboratory investigations were unremarkable. Lesion was removed with laryngeal microdebrider and three courses of intravenous dexamethasone were administered. Patient's postoperative period was uneventful and had remained disease free for 1 year. To date, no consensus has been reached on the optimal treatment of subglottic EAF. We recommend regular follow-up to detect early recurrence.